2021
DOI: 10.3390/app11199354
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Long-Term Change in the Thermal Resistance of Extruded Insulation Materials through Accelerated Tests

Abstract: Two experiments were executed to examine the slice accelerated test method, suggested in ISO 11561 “Ageing of thermal insulation materials—Determination of the long-term change in thermal resistance of closed-cell plastics (accelerated laboratory test methods)” and to observe the changes in the thermal performance of insulation material over time by the real-time ageing process. The accelerated test method was conducted for 120 consecutive days using 10 mm thick-sliced specimens, which were sampled from a 50 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…As is known, thickness has a determinant contribution to the thermal conductivity of materials and it should be taken into account when insulation capacity is being compared [ 51 , 52 ]. Therefore, to better compare the insulation capacity of the developed composite material with the conventional solutions, the thermal resistance (R) of all materials was calculated according to Equation (1) [ 51 , 52 ]: where λ 20 °C is the thermal conductivity coefficient at 20 °C (W m −1 K −1 ) and t is the thickness (m) of each material. Moreover, the thickness required to achieve a thermal resistance equivalent to rockwool and EPS was also determined for each material.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As is known, thickness has a determinant contribution to the thermal conductivity of materials and it should be taken into account when insulation capacity is being compared [ 51 , 52 ]. Therefore, to better compare the insulation capacity of the developed composite material with the conventional solutions, the thermal resistance (R) of all materials was calculated according to Equation (1) [ 51 , 52 ]: where λ 20 °C is the thermal conductivity coefficient at 20 °C (W m −1 K −1 ) and t is the thickness (m) of each material. Moreover, the thickness required to achieve a thermal resistance equivalent to rockwool and EPS was also determined for each material.…”
Section: Resultsmentioning
confidence: 99%
“…As is known, thickness has a determinant contribution to the thermal conductivity of materials and it should be taken into account when insulation capacity is being compared [51,52]. Therefore, to better compare the insulation capacity of the developed composite material with the conventional solutions, the thermal resistance (R) of all materials was calculated according to Equation (1) [51,52]: As can be observed, the developed composite material has lower thermal conductivity than plasterboard and oriented strand board (OSB) for all studied temperatures (Table 2). However, EPS and rockwool reached much lower values (Table 2).…”
Section: Insulation Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major concerns with polymeric insulation materials is their life expectancy, especially in outdoor environments, which results in thermal [ 84 ], mechanical and dielectric degradation [ 85 ] over time. In a study conducted on polymer films [ 86 ], it was shown that for a given film thickness, the aging rate increases with the ambient temperature due to the higher mobility of the charge carriers.…”
Section: Causes Of Polymer Degradationmentioning
confidence: 99%